COVERAGE OF THE SOCIO-POLITICAL AND ETHICAL PROBLEM IN THE WORKS OF ABU RAYKHAN BERUNI - Islamov Kamal Tashkulovich (Journals Park Publishing, 2022)
This article highlights the socio-political and moral problems of the author Abu Rayhan Beruni. According to Beruni, as a result of assessing people and their work and material incentives, the state will be strong, the country's managers and people's lives will be prosperous. One of the important socio-political views of Beruni is the recognition that the spiritual and material needs of people are the basis for creating a society. Material factors such as the need to satisfy needs (food, clothing, etc.) encourage people to live together. The needs are varied and innumerable. Only a few people can provide them together. To do this, people felt the need to found cities.
Keywords: needs, conditions, nutrition, clothing, person, factor, material needs, society